Foreign ownership and performance: mediating and moderating effects. Issue 2 (3rd June 2019) - Gu, Vicky Ching; Cao, Ray Qing; Wang, John
Abstract : Purpose: Although foreign ownership has been widely studied to show its impact on firm performance, the findings are mixed and the underlying rational to explain the impact is not entirely clear. The purpose of this study is to determine if there is a direct relationship between foreign ownership and performance or if this relationship is indirect and affected by mediating and moderating variables such as international diversification and competitive environment. Design/methodology/approach: Financial data, survey data and other financial measures for known indices are used in the research, and SPSS and SEM (Stata 15) analyses are used to test empirically derived hypotheses. Findings: Results from this study indicate that the relationship between foreign ownership and firm performance is mediated by international diversification, such that higher levels of both foreign corporate and foreign institutional ownership lead to higher levels of international diversification, which then lead to higher levels of firm performance. Results from this study also indicate that the competitive environment moderates the relationship between a firm's level of international diversification and performance, such that the effect of international diversification on performance is greater as the environment becomes more competitive. Practical implications: This study provides empirical evidence for managers to seriously consider the impact of foreign ownership on decisions involving international diversification, along with competitive environment, when formulating and implementing organizational strategies. Originality/value: This study extends prior research examining the effects of foreign ownership on firm performance by uniquely showing how international diversification mediates the relationship between foreign ownership and firm performance and how the competitive environment moderates the relationship between international diversification and firm performance.